2021
DOI: 10.1186/s12884-021-03904-4
|View full text |Cite
|
Sign up to set email alerts
|

The perception of Italian pregnant women and new mothers about their psychological wellbeing, lifestyle, delivery, and neonatal management experience during the COVID-19 pandemic lockdown: a web-based survey

Abstract: Background In response to the COVID-19 pandemic, drastic measures for social distancing have been introduced also in Italy, likely with a substantial impact in delicate conditions like pregnancy and puerperium. The study aimed to investigate the changes in lifestyle, access to health services, and mental wellbeing during the first Italian lockdown in a sample of Italian pregnant women and new mothers. Methods We carried out a web-based survey to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 18 publications
2
34
3
4
Order By: Relevance
“…Recent pooled prevalence, based on a rapid review of 46 studies, has cited rates of perinatal depression and anxiety during COVID-19 of 25.6% and 30.5%, respectively, more than double pre-COVID levels [ 9 ]. Moreover, anxiety and depression in new mothers who gave birth during COVID-19 was reported as high as 61.9% [ 10 ], with rates of clinically relevant depression, up to 12 weeks postpartum, of 43% [ 11 ]. The seriousness of the altered systems of care, alongside increased rates of psychological distress was highlighted in a recent Mothers and Babies: Reducing Risk through Audits and Confidential Enquiries across the UK (MBRRACE-UK) report which documented two instances where women died by suicide, as referrals to perinatal mental health services were denied or delayed because of COVID-19 related restrictions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent pooled prevalence, based on a rapid review of 46 studies, has cited rates of perinatal depression and anxiety during COVID-19 of 25.6% and 30.5%, respectively, more than double pre-COVID levels [ 9 ]. Moreover, anxiety and depression in new mothers who gave birth during COVID-19 was reported as high as 61.9% [ 10 ], with rates of clinically relevant depression, up to 12 weeks postpartum, of 43% [ 11 ]. The seriousness of the altered systems of care, alongside increased rates of psychological distress was highlighted in a recent Mothers and Babies: Reducing Risk through Audits and Confidential Enquiries across the UK (MBRRACE-UK) report which documented two instances where women died by suicide, as referrals to perinatal mental health services were denied or delayed because of COVID-19 related restrictions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the most highlighted concerns for women during this time have focused on the potential physical health risks of mother and baby contracting coronavirus [ 13 , 14 , 15 , 16 , 17 , 18 ]. There has been increasing evidence of the negative impact of the pandemic on women’s mental health and wellbeing [ 12 , 19 , 20 , 21 , 22 , 23 ]. However, studies have reported a lack of research focused on the experiences of women from minority ethnic backgrounds [ 12 , 21 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with that study, we did not find strong relationships between physical activity (whether pre-pregnancy, or postpartum) and mental health. Based on prior research in pregnant and postpartum mums internationally (11,35,36), it was anticipated that social distancing and isolation measures during COVID-19 restrictions would negatively impact the mental health of Australian postpartum mothers. Previous international research during COVID-19 has been mixed reporting depressive symptoms in the general population were worse (11,35), better (37) or the same (13).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that regular participation in physical activity can improve and maintain mental health and well-being (19-21), however, many women fail to maintain sufficient physical activity during and following pregnancy (40). Based on previous research (11,36) and given the closure of gyms and fitness facilities in Australia, it was widely anticipated that physical activity would be low during COVID-19 social distancing measures. Despite women reporting being physically active on the Godin Leisure questionnaire, on average, only 41% of the postpartum women we sampled were meeting Australian physical activity guidelines of 150 min.week −1 during COVID-19 social distancing restrictions.…”
Section: Discussionmentioning
confidence: 99%